Conflict of The Main Character In Pariban - Idola dari Tanah Jawa Movie - Alvian Ovaldo Sinambela; Anna Riana Suryanti Tambunan (TRANSFORM : Journal of English Language Teaching and Learning, 2019)
The thesis deals with Conflict of The Main Character In Pariban: Idola dari Tanah Jawa Movie. The objectives of this study were to find out the type of conflicts that faced by Halomoan as the main character in the Pariban : Idola  dari Tanah Jawa movie and to find out the causes of conflict itself. The study was conducted by using descriptive qualitative method. The data of the study were movie and the script. The researcher found that the causes of conflict experienced by Halomoan as the main character in Pariban Idola Dari Tanah Jawa Movie, among others, were his condition and his surroundings, which made him under pressure, differences in opinion with the people around him, and competition. All of it is based on Hunt and Metcalf's (1996: 97) theory about conflict.